2018
DOI: 10.1097/md.0000000000013613
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid syndrome combined with acute coronary syndrome

Abstract: Rationale:Antiphospholipid syndrome (APS) combined with acute coronary syndrome (ACS) is rarely reported.Patient concerns:One male patient with APS was admitted to our hospital, who had recent unstable angina (UA).Diagnosis:The preliminary diagnosis of ACS and UA (BraunwaldiB) was then made.Interventions:This patient received secondary preventative therapy for coronary heart disease (CHD) in combination with percutaneous transluminal coronary angioplasty (PTCA) and implantation of NeoVas Bioresorbable Coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…APS is also associated with acute myocardial infarction (AMI). This thromboembolic state caused by, endothelial cell activation, direct inhibition of the activated protein C pathway, abnormalities in platelet function and complement activation can predispose to cardiovascular events [6,17]. Up to 5.5% of cases with AMI in young individuals are secondary to APS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APS is also associated with acute myocardial infarction (AMI). This thromboembolic state caused by, endothelial cell activation, direct inhibition of the activated protein C pathway, abnormalities in platelet function and complement activation can predispose to cardiovascular events [6,17]. Up to 5.5% of cases with AMI in young individuals are secondary to APS.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 5.5% of cases with AMI in young individuals are secondary to APS. When a stent is used in a patient with APS, the antiphospholipid antibody on intima in the stent promotes atherosclerosis, restenosis as well as vein graft disease [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute coronary syndrome is uncommon in young APS patients without traditional risk factors. APS may predispose to accelerated atherosclerosis; however, cases of myocardial infarction due to microthrombosis have been described [ 8 ]. Regarding the patient’s aPL profile, the presence of more than one antiphospholipid antibody, the high titer and the persistent positivity associate with high risk for thrombosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antiphospholipid syndrome (APS) is a hypercoagulable condition defined by recurrent thrombotic episodes, including deep vein thrombosis (DVT), pulmonary embolism, placental thrombosis leading to miscarriage or arterial thrombosis, all in the presence of circulating antiphospholipid antibodies (APA). For the diagnosis of APS, the patient must have one of the following clinical presentations: arterial or venous thrombosis, pregnancy loss or thrombocytopenia, associated with at least one of the following laboratory criteria: presence of lupus antibodies, moderate/high titer of IgG/IgM anticardiolipin antibodies or IgG/IgM anti-glycoprotein B2 antibodies; each confirmed on two separate occasions with a minimum interval of 12 weeks [62][63][64].…”
Section: Antiphospholipid Syndromementioning
confidence: 99%
“…Furthermore, antiphospholipid antibodies that bind to endothelial cells inhibit prostacyclin secretion, leading to increased platelet adhesion and TF release by vascular endothelium and monocytes. As a result, protein C activity is inhibited, favoring further secretion of IAP, leading to inhibition of the fibrinolytic system [62][63][64]. A study by Gurlek et al, which included patients with CAD and APS who were treated by percutaneous coronary intervention (PCI), showed that restenosis rates at 1-year follow-up were significantly higher for those patients who had moderate or high titers of anticardiolipin antibodies.…”
Section: Antiphospholipid Syndromementioning
confidence: 99%